Neutron Activation Analysis of Aegean-style IIIC Pottery from Maa: Palaeokastro, Cyprus, and a Discussion on the Foundation of the Site - Mountjoy, Penelope A. (Ägypten und Levante, 2020)
Neutron Activation Analysis was carried out in Bonn on 12th century BC Aegean-style pottery from Maa: Palaeokastro. The results gave rise to a survey of maritime trade at Maa and of winds and currents in the east Mediterranean, leading to a discussion of the date and reason for the foundation of the site.